Calcifying aponeurotic fibroma of the thigh: A differential diagnosis for infant knee contracture and leg length inequality (a case report). (2020) - Zhang, Liuzhe; Kobayashi, Hiroshi; Ikegami, Masachika; Ohki, Takahiro; Shinoda, Yusuke; Tanaka, Sakae; Kawano, Hirotaka
Highlights: Calcifying aponeurotic fibroma is a rare tumor primarily in the distal extremities. Very rarely, this tumor can cause infant knee contracture and leg length inequality. The mechanism may be fascia adhesion and increased blood flow around the metaphysis. Timely diagnosis and appropriate surgical intervention may improve functional prognosis. Abstract: Introduction: Calcifying aponeurotic fibroma is an uncommon type of tumor that primarily occurs in the distal extremities of young children. It usually appears as a slow-growing and asymptomatic soft-tissue mass and rarely causes complications, such as joint contractures. Presentation of case: We present a case of calcifying aponeurotic fibroma that caused knee contracture and leg length inequality, in which the affected leg was longer than the other. On the patient's first visit to our hospital at 8 years of age, a solid nodule was palpable at the medial distal area of her right thigh. Magnetic resonance imaging showed a T1WI-low, fs-T2WI-slightly high 60-mm lesion on the vastus intermedius muscle with enhancement caused by a gadolinium agent. Tumor resection surgery, which was preceded by an incisional biopsy that resulted in calcifying aponeurotic fibroma, improved the knee's range of motion (extension-flexion improved from 0–80° to 0–120°). For the remaining leg length inequality of 35 mm, epiphyseal arrest surgery is planned. Discussion and conclusion: Very infrequently, calcifying aponeurotic fibroma can cause infant knee contracture and leg length inequality. These symptoms were seemingly caused, respectively, by fascia adhesion and by increased blood flow around the metaphysis. Timely diagnosis and appropriate surgical intervention may improve functional prognosis in affected patients.